Etnobotani pada Upacara Adat Suku Sasak - Roshiya Hilyatiy; Nining Purwati (Yayasan Ekologi Masyarakat dan Sains, 2026)
Ethnobotany is the study related to the use of plants by humans in a custom or culture. The purpose of this research is to identify the types of plants used by the Sasak tribe and their symbolic meanings in various traditional ceremonies of the Sasak tribe, namely the peraq api, ngurisan and begawe merik ceremonies. In this study, the method used is qualitative descriptive. The results of the study show that there are 41 types of plants used in the three traditions, but the most is in the tradition of begawe merart, which is as many as 19 types of plants followed by peraq api, which is 13 types of plants, finally the ngurisan tradition utilizes 9 types of plants. The use of these plants is diverse, namely as food offerings and certain traditional symbols that have symbolic meanings believed by the Sasak tribe people themselves. This is an effort to preserve the noble values contained in each tradition and plants, especially plants used in traditional ceremonies so that they can be used for continuity.